Functional identification of PGM1 in the regulating development and depositing of inosine monophosphate specific for myoblasts - Zhao, Wei; Cai, Zhengyun; Wei, Chuanhao; Ma, Xiaoping; Yu, Baojun; Fu, Xi; Zhang, Tong; Gu, Yaling; Zhang, Juan (Frontiers in Veterinary Science, 2023)
As an intermediate product of purine metabolism, inosine monophosphate (IMP) naturally exists in the muscle of livestock and poultry and plays a key role in the flavor of livestock and poultry meat. In this study, we performed proteome and metabolome analyses on the leg muscle, compared to the breast muscle control of 180-day-old Jingyuan chickens (hens), which had different IMP content. The key candidate genes identified by a differential analysis were verified to be associated with regulation of IMP-specific deposition. The results showed that the differentially expressed (DE) proteins and metabolites jointly involve 14 metabolic pathways, among which the purine metabolic pathway closely related to IMP synthesis and metabolism is enriched with four DE proteins downregulated (with higher expression in breast muscles than in leg muscles), including adenylate kinase 1 (AK1), adenosine monophosphate deaminase 1 (AMPD1), pyruvate kinase muscle isoenzyme 2 (PKM2) and phosphoglucomutase 1 (PGM1), six DE metabolites, Hypoxanthine, Guanosine, L-Glutamine, AICAR, AMP and Adenylsuccinic acid. Analysis of PGM1 gene showed that the high expression of PGM1 promoted the proliferation and differentiation of myoblasts and inhibited the apoptosis of myoblasts. ELISA tests have shown that PGM1 reduced adenosine triphosphate (ATP) and IMP and uric acid (UA), while enhancing the biosynthesis of hypoxanthine (HX). In addition, up-regulation of PGM1 obviously inhibited purine metabolic pathway and IMP de novo synthesis pathway, but promoted the salvage synthesis pathway. This study preliminarily explored the mechanism of action of PGM1 in regulating the growth and development of myoblasts and specific IMP deposition in Jingyuan chickens, which provided certain theoretical basis for the development and utilization of excellent traits in Jingyuan chickens.